Analysis of The Effect of Exchange Rates, E-Money and Interest Rates on The Amount of Money Supply and Its Implications on The Inflation Level in Indonesia 2012-2017 Period - Rizal Ramadhani; Widyo Nugroho (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
This study aims to find out and test the partial influence of exchange rate variables, Electronic Money (e-money), interest rates on money supply; and the partial effect of variable exchange rates, e-money, interest rates, and the amount of money supply toward the inflation rate. This research method is quantitative, with a type of causal research. The geographical scope of the study is Indonesia with a six-year period (2012-2017). Based on the periodization, by using monthly data, each variable has 72 data (n = 72), which is 6 years x 12 months. The data used was secondary data. The multiple linear regression analysis was used to test seven hypotheses all of which are bivariate models. The results show that the exchange rate (USD to IDR exchange rate) has a positive and significant effect on the money supply. E-money has a positive and significant effect on the money supply. Interest rates have a negative effect, but are not significant for the money supply. Exchange rates have a negative effect, but not significant to inflation. E-money has a negative effect but not significant on inflation. Interest rates have a positive effect but not significant on inflation. Money supply has a negative effect but not significant on inflation. Keywords: exchange rate, e-money, money supply, interest rates, and inflation